Pengaruh Pemahaman Auditor dan Pengalaman Auditor terhadap Pendeteksian Kecurangan yang Dimediasi oleh Kualitas Audit (Studi Empiris pada Kantor Akuntan Publik Kota Malang) - Kelana, Tomas Aldi; Gunadi, Gunadi; Lisa, Oyong; Hertanto, Ronny Hendra (Universitas Syiah Kuala, 2025)
This study aims to analyze the influence of auditor understanding on fraud detection, analyze the influence of auditor experience on fraud detection, analyze the influence of auditor understanding on audit quality, analyze the influence of auditor experience on audit quality, analyze the influence of audit quality on fraud detection, analyze the indirect influence of auditor understanding on fraud detection through audit quality, and analyze the indirect influence of auditor experience on fraud detection through audit quality. This study is quantitative with an associative approach. The study population is auditors working in Public Accounting Firms (KAP) throughout Malang Raya that are registered with the Financial Services Authority (OJK) and hold a Registration Certificate (STT) from the Supreme Audit Agency (BPK). The sampling technique used purposive sampling with specific criteria, resulting in a total of 52 respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling with the aid of SmartPLS software. The results showed that auditor understanding had a significant positive effect on fraud detection, auditor experience had a significant positive effect on fraud detection, auditor understanding had a significant positive effect on audit quality, auditor experience had a significant positive effect on audit quality, audit quality had a significant positive effect on fraud detection, auditor understanding had a significant effect on fraud detection through audit quality, and auditor experience had a significant effect on fraud detection through audit quality.